Pre-Visit Use of Non-Prescribed Antibiotics among Child Patients in China: Prevalence, Predictors, and Association with Physicians' Prescribing of Antibiotics at Medical Visits - Nan Christine Wang (MDPI AG, 2022)
Antibiotic resistance is one of the most serious global public health crises. Inappropriate use of antibiotics is an important contributor. Using a cross-sectional survey, we recruited 3056 caregivers from 21 provinces in China to complete a questionnaire pertaining to their most recent medical visits for children's acute respiratory tract infection (ARTI) symptoms in October 2013. The findings show that the prevalence of caregivers giving children non-prescribed antibiotics before their medical visit was as high as 38%. Caring for an older child and having lower educational attainment increased the likelihood of self-medication with antibiotics; among Chinese residential areas, caregivers living in tier 2 urban districts were most likely to administer non-prescribed antibiotics before their visit. Physicians' prescribing of antibiotics was significantly associated with caregivers' self-reported pre-visit use of non-prescribed antibiotics. Misuse should be addressed by regulating the sale of antibiotics and improving communication at medical consultations.